Impact of standard test protocols on sporicidal efficacy. Issue 3 (July 2016) - Wesgate, R.; Rauwel, G.; Criquelion, J.; Maillard, J.-Y.
Summary: Background: There has been an increase in the availability of commercial sporicidal formulations. Any comparison of sporicidal data from the literature is hampered by the number of different standard tests available and the use of diverse test conditions including bacterial strains and endospore preparation. Aim: To evaluate the effect of sporicidal standard tests on the apparent activity of eight biocides against Clostridium difficile and Bacillus subtilis . Methods: The activity of eight biocidal formulations including two oxidizing agents, two aldehydes, three didecyldimethylammonium chloride (DDAC) and amine formulations, and sodium hypochlorite were evaluated using four standard sporicidal tests (BS EN 14347, BS EN13704, ASTM E2197-11, and AOAC MB-15-03) against B. subtilis (ACTC 19659) and C. difficile (NCTC 11209) spores. Findings: C. difficile spores were more susceptible to the sporicides than were B. subtilis spores, regardless of the method used. There were differences in sporicidal activity between methods at 5 min but not at 60 min exposure. DDAC and amine-based products were not sporicidal when neutralized appropriately. Neutralization validation was confirmed for these biocides using the reporting format described in the BS EN standard tests, although the raw data appear to indicate that neutralization failed. Conclusion: The different methods, whether based on suspension or carrier tests, produced similar sporicidal inactivation data. This study suggests that detailed neutralization validation data should be reported to ensure that neutralization of active spores is effective. Failure to do so may lead to erroneous sporicidal claims.